2018
DOI: 10.1186/s12894-018-0402-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 90-day and long-term mortality in octogenarians undergoing radical cystectomy

Abstract: BackgroundRadical cystectomy bears a considerable perioperative mortality risk particularly in elderly patients. In this study, we searched for predictors of perioperative and long-term competing (non-bladder cancer) mortality in elderly patients selected for radical cystectomy.MethodsWe stratified 1184 consecutive patients who underwent radical cystectomy for high risk superficial or muscle-invasive urothelial or undifferentiated carcinoma of bladder into two groups (age < 80 years versus 80 years or older). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Data were reviewed for preoperative characteristics (age, gender, body mass index [BMI], neoadjuvant chemotherapy [NAC], American Society of Anesthesiologists [ASA] score), operative variables (operation time [skin-to-skin], EBL, type of diversion), and postoperative outcomes (staging, lymph node yield/invasion and LOS). A cut-off age of ≥80 years was used to define elderly patients [5,[15][16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…Data were reviewed for preoperative characteristics (age, gender, body mass index [BMI], neoadjuvant chemotherapy [NAC], American Society of Anesthesiologists [ASA] score), operative variables (operation time [skin-to-skin], EBL, type of diversion), and postoperative outcomes (staging, lymph node yield/invasion and LOS). A cut-off age of ≥80 years was used to define elderly patients [5,[15][16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…It is obvious that the predicted values of the survival analyses of the scoring systems vary in every study (4,12,16). As a matter of fact elder age (≥75), it has been reported that progressive cancer stages (T3-4) and high ASA score (≥3), increase the perioperative mortality within the 90 days period (4); make a negative impact of the five-years OS ratios through ACCI (17) and ECOG score has no additional contribution for the prediction of the 90 days mortality (4).…”
Section: Discussionmentioning
confidence: 99%
“…al (12), ASA and ECOG scores make an impact on both the 90-days perioperative mortality and the five years OS, on the other hand ACCI predicts the OS in a much more meaningful manner. Froehner et al (16) have specified that ACCI and ASA scores fail to predict the short and long-term mortality for the patients aged 80 and more, after cystectomy. According to the multivariate analysis in our study, we observed that advanced tumor stage (T3-4) and ECOG score affect PFS more significantly, and ASA score affects OS more significantly, while we could not determine the effect of patient age on oncological results.…”
Section: Discussionmentioning
confidence: 99%
“…709 studies were extracted from the search of which 19 were deemed suitable for inclusion (Table 3). These studies included 1 review 45 and 18 cohort studies [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] (of which eight were from single-center data) 63 ).…”
Section: Comorbidities and Survivalmentioning
confidence: 99%
“…For all MIBC patients and those undergoing curative treatment (radical cystectomy or external beam radiotherapy), 12 of the studies concluded an association between increasing comorbidity (as defined by each study) and an increased risk of overall death. [48][49][50][53][54][55][56][57][58][59][60]62 Three studies stated the same direction of association for cancer-specific death. 54,57,61 The ways in which the studies measured comorbidity for the radical cystectomy patients varied as can be seen in Table 3.…”
Section: Comorbidities and Survivalmentioning
confidence: 99%